2019
DOI: 10.1108/maj-03-2018-1835
|View full text |Cite
|
Sign up to set email alerts
|

The role of accounting in conflicts resolution

Abstract: Purpose This study aims to examine an alternative use of accounting information and technology (forensic audit) for resolving conflicts between two government agents and consequently enhancing accountability in Nigeria. Design/methodology/approach The study adopts contextualised explanation of case study theorising. Data for the study were gathered from two primary documents: the forensic audit report of PricewaterhouseCoopers (PwC) and the report of the Senate Committee on Finance and Appropriation. The the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The benefit of forensic accountants to society may also be seen in their role of facilitating resolutions to commercial and family disputes, enhancing public awareness of fraud risks and helping government agencies in solving vexed financial matters. This finding is consistent with many previous studies on forensic accounting’s role in society (Abdul-Baki, 2019; DiGabriele and Lohrey, 2016; Sahdan et al , 2020). This finding explains that forensic accounting services are directly related to people and organization problems.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The benefit of forensic accountants to society may also be seen in their role of facilitating resolutions to commercial and family disputes, enhancing public awareness of fraud risks and helping government agencies in solving vexed financial matters. This finding is consistent with many previous studies on forensic accounting’s role in society (Abdul-Baki, 2019; DiGabriele and Lohrey, 2016; Sahdan et al , 2020). This finding explains that forensic accounting services are directly related to people and organization problems.…”
Section: Discussionsupporting
confidence: 93%
“…One practitioner indicated that forensic accountants engage in family law services, which result in the prevention of “bankruptcy,” “[reduce dramatically divorces and] reduce family separations,” “stress” and, in some cases, prevention of “suicides cases” (P2). The forensic accountant can do so through mediation and arbitration effort (Abdul-Baki, 2019; Brennan, 2005). In addition, forensic accountants facilitate the resolution of commercial disputes by providing solid advice and accurate analysis to the individuals and companies in that process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forensic accounting, described as a problem-solving tool by Prabowo (2021), requires adaption to changes and developments in practice. Investigation of fraud, litigation, valuation of businesses and information technology (IT) forensic accounting are among the topics covered in most forensic accounting courses, as noted by Abdul-Baki (2021), Elder and Yebba (2017), Honigsberg (2020), Jalilvand and Kostolansky (2016), Odia and Akpata (2021) and Rezaee and Wang (2019).…”
Section: Literature Reviewmentioning
confidence: 99%